2011
DOI: 10.1016/j.pneurobio.2011.07.003
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic synchronization in the limbic system and its role in the generation of epileptiform activity

Abstract: GABA is the main inhibitory neurotransmitter in the adult forebrain, where it activates ionotropic type A and metabotropic type B receptors. Early studies have shown that GABA A receptormediated inhibition controls neuronal excitability and thus the occurrence of seizures. However, more complex, and at times unexpected, mechanisms of GABAergic signaling have been identified during epileptiform discharges over the last few years. Here, we will review experimental data that point at the paradoxical role played b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
253
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 227 publications
(279 citation statements)
references
References 316 publications
(436 reference statements)
24
253
1
Order By: Relevance
“…Indeed, early work in the in vitro hippocampal slice preparation demonstrated that interictal-like (hereafter referred to as interictal) epileptiform activity results from weakened inhibition (Johnston and Brown, 1981;Prince, 1978, 1980) but later, by employing experimental procedures that enhance GABAergic signaling such as the K + channel blocker 4-aminopyridine (4AP) or Mg 2+ free medium, we and other investigators have reported that ictal-like (hereafter referred to as ictal) discharges in adult rodents are paradoxically contributed by GABA A receptor-mediated signaling (see for review Avoli and de Curtis, 2011). In addition, under specific pharmacological manipulations, GABA A receptor-mediated currents are the sole synaptic mechanism contributing to ictogenesis in the hippocampus (Uusisaari et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, early work in the in vitro hippocampal slice preparation demonstrated that interictal-like (hereafter referred to as interictal) epileptiform activity results from weakened inhibition (Johnston and Brown, 1981;Prince, 1978, 1980) but later, by employing experimental procedures that enhance GABAergic signaling such as the K + channel blocker 4-aminopyridine (4AP) or Mg 2+ free medium, we and other investigators have reported that ictal-like (hereafter referred to as ictal) discharges in adult rodents are paradoxically contributed by GABA A receptor-mediated signaling (see for review Avoli and de Curtis, 2011). In addition, under specific pharmacological manipulations, GABA A receptor-mediated currents are the sole synaptic mechanism contributing to ictogenesis in the hippocampus (Uusisaari et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In line with this view, measurements of the extracellular [K + ] elevations associated with the "slow" 4AP-induced interictal events occurring during blockade of glutamatergic transmission have shown larger values in juvenile than in adult hippocampal slices (Avoli et al, 1996b). However, in line with what originally reported by Galvan et al (1982), ictal-like activity is readily generated in response to 4AP application by neuronal networks in several limbic and extralimbic structures such as the rhinal cortices, the amygdala, and the insular or cingular cortices (Avoli et al, 1996a;Brückner and Heinemann, 2000;Klueva et al, 2003; see for review Avoli and de Curtis, 2011). By employing the in vitro isolated hippocampus from new-born rats Luhmann et al (2000) have shown that 4AP can induce interictal and ictal discharges in the CA3 area as well as that these events can propagate to the entorhinal cortex when animals older than 3 days are used.…”
Section: K + Channel Blockersmentioning
confidence: 61%
“…As discussed above, slow interictal discharges induced by 4AP are associated with transient increases in extracellular [K + ] due to the activation of GABA A receptors (Morris et al, 1996) and more specifically to the activation of the KCC2 co-transporter, which causes the extracellular efflux of both K + and Cl − (Viitanen et al, 2010). As reviewed by Avoli and de Curtis (2011), such increases in extracellular K + are expected to depolarize neighbouring neurons, to promote ectopic spike generation, and to shift the reversal potential of GABA A receptor-mediated IPSPs in a positive direction, thus weakening inhibition. All these mechanisms, which are paradoxically initiated by the activation of GABA A receptor signalling, are known to increase neuronal excitability and are thus likely to promote ictogenesis in the 4AP in vitro brain slice model.…”
Section: K + Channel Blockersmentioning
confidence: 99%
See 2 more Smart Citations